Clinical efficacy of cefpodoxime proxetil against community-acquired pneumonia - Niki, Yoshihito; Kawanishi, Masayoshi (Japanese Journal of Chemotherapy, 2005)
A therapeutic guide to community-acquired pneumoniae is presented in the Manual of Prescriptions for Antibacterial Drugs, edited by the Japanese Association for Infectious Diseases and the Japanese Society of Chemotherapy. Based on this manual and working mainly in general hospitals, we studied the clinical efficacy of cefpodoxime proxetil (CPDX-PR), one of the first-line drugs for ambulatory patients with community-acquired pneumonia categorized as Class I and Class II in the manual, and verified the accuracy of the manual as a therapeutic guide. Among the 247 subjects assessed for efficacy, CPDX-PR was effective in 3-6 days in 83.1%(133/160) of patients categorized as “excluded indeterminate”. Among the 133 judged as “effective”, we evaluated “cured or improved” in community-acquired pneumonia and found that “cured or improved” was 99.0%(102/103) in 7-10 days in patients categorized as “excluded indeterminate”. In 11 of 27 judged “ineffective”, CPDX-PR was continued or ended without changing prescriptions to other antibacterial drugs. Of these 11, 9 categorized as “excluded indeterminate” were assessed as “cured or improved” in the last treatment assessment. Of the 263 patients assessed in the safety analysis, 1 reported adverse events-mild GOT and increased GPT-, but recovered rapidly after CPDX-PR was discontinued. We thus confirmed that CPDX-PR is clinically highly effective and safe in the treatment of communityacquired pneumonia, and that criteria for efficacy in the manual were useful in assessing community-acquired pneumonia patients in the early stages of illness. We also found, however, that reconsidering criteria for changing prescriptions to other antibacterial drugs would improve the accuracy of the manual, because some patients among those treated as “ineffective” recovered without changing to other antibacterial drugs.